Quantification of pulmonary perfusion in idiopathic pulmonary fibrosis with first pass dynamic contrast-enhanced perfusion MRI. Issue 2 (3rd December 2020) - Weatherley, Nicholas D; Eaden, James A; Hughes, Paul J C; Austin, Matthew; Smith, Laurie; Bray, Jody; Marshall, Helen; Renshaw, Stephen; Bianchi, Stephen M; Wild, Jim M
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a fatal disease of lung scarring. Many patients later develop raised pulmonary vascular pressures, sometimes disproportionate to the interstitial disease. Previous therapeutic approaches that have targeted pulmonary vascular changes have not demonstrated clinical efficacy, and quantitative assessment of regional pulmonary vascular involvement using perfusion imaging may provide a biomarker for further therapeutic insights. Methods: We studied 23 participants with IPF, using dynamic contrast-enhanced MRI (DCE-MRI) and pulmonary function tests, including forced vital capacity (FVC), transfer factor (TLCO ) and coefficient (KCO ) of the lungs for carbon monoxide. DCE-MRI parametric maps were generated including the full width at half maximum (FWHM) of the bolus transit time through the lungs. Key metrics used were mean (FWHMmean ) and heterogeneity (FWHMIQR ). Nineteen participants returned at 6 months for repeat assessment. Results: Spearman correlation coefficients were identified between TLCO and FWHMIQR (r=−0.46; p=0.026), KCO and FWHMmean (r=−0.42; p=0.047) and KCO and FWHMIQR (r=−0.51; p=0.013) at baseline. No statistically significant correlations were seen between FVC and DCE-MRI metrics. Follow-up at 6 months demonstrated statistically significant decline in FVC (p=0.040) and KCO (p=0.014), with an increase in FWHMmean (p=0.040), but no significant changes in TLCO (p=0.090) nor FWHMIQR (p=0.821). Conclusions: DCE-MRI first pass perfusion demonstrates correlations with existing physiological gas exchange metrics, suggesting that capillary perfusion deficit (as well as impaired interstitial diffusion) may contribute to gas exchange limitation in IPF. FWHMmean showed a significant increase over a 6-month period and has potential as a quantitative biomarker of pulmonary vascular disease progression in IPF.